Enrichment Effect of Artemia sp. with Fruktooligosaccharides to enhance Growth, Survival Rate and Digestive enzyme of Litopenaeus vannamei Larvae - Ditya Nurbaeti; Achmad Noerkhaerin Putra (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
Larvae are the most critical stage in the life stages of fish and shrimp due to the high mortality at this stage. The aim of this study was to evaluate the enrichment effect of Artemia sp. as live feed using different doses of Fructooligosaccharides (FOS) on the growth, survival rate and amylase, protease and lipase enzymes of vannamei larvae. Four Artemia sp. enrichments with different doses of FOS (P0: 0%, P1: 1.3%, P2: 1.5%, P3: 1.7%) were fed to vannamei larvae. The absolute weight, absolute length, daily growth rate, and protease activity of enrichment treatments were higher (P<0.05) than without enrichment. There are no differences (P>0.05) in protease activity of vannamei larvae between P2 and P3 treatment. Artemia sp. enrichment using different doses of FOS can increase the growth and protease enzyme activity of white shrimp larvae. The growth, protease and amylase activity of vaname larvae are improved with increasing FOS enrichment dose on Artemia sp. The FOS enrichment dose of 1.7% is the best because it can produce the best growth performance, survival rate and digestive enzyme activity.